GAGASAN KEARIFAN LOKAL: PENDAMPINGAN PELATIHAN BATIK KREATIF DI ATAS KAYU DI KAMPUNG BATIK PASIRAN - Belinda Sukapura Dewi; Ariesa Pandanwangi; Dewi Isma Aryani; Rosida Tiurma Manurung; Ida Ida (Jurnal Abdimas Bina Bangsa, 2023)
The Sundanese Wiwitan people in the Pasiran Traditional Village, Garut Regency, live in the present era with diverse livelihoods. The rich potential of nature made her creative to put it into batik motifs, so that in 2010, the women started learning traditional batik. Based on this condition, the local government seeks to improve community skills through collaboration with many parties who are directly fostered by community leaders. The problem faced by partners is the development of the potential of batik by utilizing materials in the Pasiran Traditional Village environment. The goal is to increase skills so that economic conditions can also develop. The method used is the mentoring and evaluation method through distributing questionnaires with a Likert scale before and after the activity. There were 19 participants who took part in this training and from the results of SPSS processing using the Wilcoxon sign-rank test method, it was found that there were differences in knowledge before and after mentoring with a significance level of 0.00 > 0.05 and all 19 participants experienced increased knowledge after mentoring